ANALISIS PENGARUH DIGITAL MARKETING DAN INFLUENCER MARKETING TERHADAP KEPUTUSAN PEMBELIAN DENGAN BRAND TRUST SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Konsumen Produk Oriflame di Kota Semarang) - Trifiana, May Lisa; Wahyuningsih, Susanti; Widodo, Untung (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2025)
This study aims to explain the influence of Digital Marketing and Influencer Marketing on Purchasing Decisions through Brand Trust as an intervening variable on Oriflame product consumers in Semarang City and to determine the influence of Digital Marketing, Influencer Marketing, and Brand Trust on Purchasing Decisions. The research method used is Path Analysis. The population of this study is Oriflame product consumers in Semarang City. The sample in this study amounted to 114 people using a non-probability sampling technique with a purposive sampling approach, namely the study selected samples intentionally and subjectively. The data collection method is by distributing questionnaires via Google Form.The types of data used are primary and secondary data. Based on the results of the analysis, it shows that: Digital Marketing has a positive and significant effect on Brand Trust as evidenced by the t-value of 2.311> t table 1.658 and a significance level of 0.023 <0.05. Influencer Marketing has a positive and significant effect on Brand Trust as evidenced by the t-value of 8.308> t table 1.658 and a significance level of 0.000 <0.05. Digital Marketing has a positive and significant effect on Purchasing Decisions as evidenced by the t-value of 2.281> t table 1.658 and a significance level of 0.024 <0.05. Influencer Marketing has a positive and significant effect on Purchasing Decisions as evidenced by the t-value of 2.281> t table 1.658 and a significance level of 0.024 <0.05. Brand Trust has a positive and insignificant effect on Purchasing Decisions as evidenced by the calculated t value of 1.683> t table 1.658 and a significant level of 0.095> 0.05. Digital Marketing does not have a positive and significant effect on Purchasing Decisions through Brand Trust as evidenced by the Direct Influence value of 0.141> Indirect Influence of 0.0222. Influencer Marketing does not have a positive and significant effect on Purchasing Decisions through Brand Trust as evidenced by the Direct Influence value of 1.003> Indirect Influence of 0.1260.Keywords: Digital Marketing, Influencer Marketing, Brand Trust and Purchasing Decisions.